KOMUNIKASI KAUM TAREKAT STUDI TENTANG POLA-POLA KOMUNIKASI DALAM KELOMPOK TAREKAT QADIRIYAH NAQSYABANDIYAH DI PESANTREN SURYALAYA TASIKMALAYA - Asep Shalahudin (Indonesian Journal of Dialectics, 2013)
This study is qualitative using phenomenological, symbolic interaction, and hermeneutic approaches. Based on the proposed descriptions, the author found that communications in Tarekat Qadiriyah Naqsyabandiyah Suryalaya, phenomenologically, describe a communication event which reflects an esoteric rite identity of religious doctrine (Islam). This esoteric rite identity of religious doctrine is formulated in symbolic form and addressed as a medium to achieve the high potential and the purpose in life. The symbol formation in this tarekat community serves as a fundamental process of determinations, thoughts, and actions. Through this symbolization as well, Tarekat Qadiriyah Naqsyabandiyah community communicates, as reflected in their convocation ceremony. This tarekat ceremony shows objective symbol orders. These symbols not only express a behavior andfeeling but also form a personal disposition from brothers (ikhwan) followed their teacher models (mursyid) or saint models orwali (holy man) derived through mythological stories. Tarekat Qadiriyah Naqsyabandiyah gives the meaning of growingcommunication as the complex one. The meaning and the comprehension of communication holds subjectively, humanistically, aesthetically, philosophically, and religious esoteric oriented. Ikhwan "reads" all communication whether among them or mubaligh, wali talqin, and mursyid as an encounter with the sacred one from past to present and through their experiences (the experiences in general terms; economic, politic, culture, especially religion). They let their object of interpretation appear as a truth, namely religious phenomenon. They interpret Tarekat as "creative" religion with the ability to transform consciousness. Ultimately, these communications that have been implemented in these rites of tarekat, is positioned not only as a lesson but also as a spiritual technique. These are considered to modify its quality of existence. The communication process and this 'meaning' seems paradoxical because the movement is not only in communication field but also in "meta-communication". Thecommunication pattern of Tarekat Qadiriyah Naqsyabandiyah is integrated centralist. This pattern is centered on one figure(mursyid) and integrated with the doctrine considered as "ideology". This ideology is reconciled to Arab's thought tradition hesitance and combined with local culture. This pattern is shown by tarekat community that makes mursyid their idol that must be followed by all of his speech and action. Besides mursyid, there are other figures that have strategic position in Tarekat Qadiriyah Naqsyabandiyah community, namely are "vice talqin". Vice talqin has four types; (1) intellectual academic/modernist; (2) traditionalist-ulama; (3) neo-traditionalist scholar; and (4) conservative traditionalist. The third figure is mubaligh. There arefour types of mubaligh: (1) pesantren mubaligh; (2) campus mubaligh; (3) politic mubaligh; and (4) stage mubaligh; formal and non-formal. The last figure is the most in quantities, it is ikhwan with types: (1) pragmatist; (2) ideologist with tends toward academic and populist.Keyword: Tarekat community, symbol, social-ritual communication